ANALISIS OCCUPATIONAL CRIME TERHADAP PRAKTIK MARK DOWN DALAM DOKUMEN KAPAL PENANGKAP IKAN - Adi Yulianto (Jurnal Kriminologi Indonesia, 2017)
This article discusses the existence of fraudulent practices in terms of decreasing (MarkDown) the size of ships on the manufacture of fishing documents, which gives a significant impact on the country and social life. The practice of this Mark Down is done by the ship owner to gain some profit, which then manipulation of the size of the vessel is facilitated by some person. therefore, this study focuses on the same person that facilitate the practice of Mark Down by analyzing using the concept of Occupational Crime. By analyzing using occupational crime concept, the researcher got the result that the practice of Mark Down as a form of occupational crime activity. Because there is some person have the status of workers, such as one of them as an employee of sea transportation. And from the practice of Mark Down is associated with Social Exchange Theory, because in practice there is a mutual social exchange between officers with ship owners to manipulate ship documents. The data to analyze obtained are secondary data from the Ministry of Marine Affairs and Fisheries, some collections of news, and previous research.